2023
DOI: 10.1111/pan.14662
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative clear fluid fasting and endoscopy‐measured gastric fluid volume in children

Abstract: Background:In light of new recommendations to shorten clear fluid fasting time before anesthesia, our study aimed at exploring residual fluid volume in the stomach after different fasting times. We intended to perform direct endoscopic aspiration of stomach contents under vision, as part of routine gastroscopy assessment. Hereby we would be able to quantify true residual gastric fluid volume and acidity in children and measure their correlation with fasting times. Methods:The study was performed as a single-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Our approach to measuring the gastric fluid volume via CT imaging, which is a standard and accepted technique for volume measurement in radiology [ 9 , 10 ] and bariatric surgery [ 11 ], was different from the methods used in previous studies, which measured gastric fluid volumes by using blind aspiration of the gastric contents [ 21 , 22 ], ultrasound assessment [ 28 , 29 , 31 ], or magnetic resonance imaging [ 27 ]. This was a practical choice because all our study patients were undergoing abdominal CT scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach to measuring the gastric fluid volume via CT imaging, which is a standard and accepted technique for volume measurement in radiology [ 9 , 10 ] and bariatric surgery [ 11 ], was different from the methods used in previous studies, which measured gastric fluid volumes by using blind aspiration of the gastric contents [ 21 , 22 ], ultrasound assessment [ 28 , 29 , 31 ], or magnetic resonance imaging [ 27 ]. This was a practical choice because all our study patients were undergoing abdominal CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…The mean pH of the residual gastric fluid was 1.5 (SD 0.9). A reverse correlation (r = −0.236, p = 0.01) between residual gastric volume and pH indicates that a lower pH was correlated with larger volumes [ 31 ]. Another prospective clinical trial comparing gastric pH and residual volume after one vs. two hours of preoperative clear fluid fasting in 131 children (ASA I or II) aged 1.01 to 16.23 years showed that one hour of clear fluid fasting does not alter gastric pH or residual volume significantly compared with fasting for two hours [ 30 ] The mean gastric pH in the one-hour fasting group was 1.44 (SD 0.26) [ 30 ] The mean pH of the residual gastric fluid in our study was higher, at 2.14 (SD 1.23), than the previously mentioned studies and did not correlate with age, weight, or time from the end of contrast [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, Maltby et al [ 10 ] challenged the overnight fasting routine, who found no correlation between gastric volume or pH values with the ingestion-surgery interval in patients given 150 ml of water. Aschkenasy et al [ 11 ] also found that drinking water at different fasting times did not have a significant correlation with gastric residual fluid. Although aspiration can lead to aspiration pneumonia and ultimately death, the incidence is relatively very low at around 0.014% [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%